Molecular tumor testing in patients with Lynch-like syndrome reveals a de novo mosaic variant of a mismatch repair gene transmitted to offspring - Guillerm, Erell; Svrcek, Magali; Bardier-Dupas, Armelle; Basset, Noémie; Coulet, Florence; Colas, Chrystelle (European journal of human genetics : EJHG, 2020)
In Lynch-like syndrome, patients have tumors with microsatellite instability but no germline pathogenic variant in mismatch repair genes or somatic methylation of the MLH1 promoter. Identification of the mechanism that causes these tumors is crucial for guiding screening of the patients and their relatives. Double somatic hits are the usual explanation for these cases; however, we have previously reported a de novo mosaic pathogenic variant in a patient with Lynch-like syndrome. Using tumoral NGS analysis of a series of 16 patients with Lynch-like syndrome, we found six patients with double somatic hits, including one patient with mosaicism of a de novo pathogenic variant in MSH2. This variant was transmitted to the patient's offspring, which has significant implications for genetic counseling.